Pemetaan Wilayah Persebaran Padi dan Kopi dengan Quantum Geographic Information System Versi 3.12.2 - Ira Zulfa; Fajrillah; Richasanty Septima; May Handri; Ida Zulfida; Lili Suryati (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
QGIS is a Geographic Information System (GIS) software used to analyze and map geographic data. In the context of mapping the distribution of rice and coffee, QGIS can be used to extract spatial data related to factors such as soil type, climate, elevation, or other environmental factors that affect the distribution and growth of these plants. analyzed. This study used QGIS software version 3.12.2 to map the distribution areas of rice and coffee. Rice and coffee are two important crops in agriculture and understanding their distribution can help in farm management and planning. The mapping methods used may include spatial data analysis, including using available spatial data such as satellite imagery or field data to identify and map areas suitable for rice and coffee cultivation and production. Paddy and coffee line mapping can provide an overview of growth patterns, availability of suitable land, or other environmental factors that affect the production of these crops. This information can be used in making decisions about agricultural development, resource allocation or sustainable development planning. ith using QGIS, agricultural researchers or practitioners can combine data from various sources, including satellite imagery, field data, or other data, to build maps that depict areas where rice and coffee grow well. This information can provide insight into crop distribution patterns, identify potential areas for agricultural development, or assist in making decisions regarding agricultural land management.